Effects of low and high irradiation levels on growth and PSII efficiency in Lemna minor L. - Lepeduš, Hrvoje (Array, 2020)
Plant growth and reproduction depend on light energy that drives photosynthesis. In the present study we compared growth characteristics, photosynthetic pigments content and photosystem II (PSII) performance in Lemna minor L. grown in two different irradiation regimes: low light (LL) – 50 μmolPHOTONS m-2 s-1 and high light (HL) – 500 μmolPHOTONS m-2 s-1. The main goal was to investigate the photosynthetic regulatory mechanisms that ensure adjustment to different light conditions and integrate these observations with the data on plant multiplication and biomass production. For this purpose, we measured chlorophyll (Chls) and carotenoid (Cars) contents and analyzed the energy fluxes through the PSII by saturation pulse method as well as by Chl a transient induction and JIP test. In a comparison of the effect of LL and HL on plant multiplication and fresh biomass, it was shown that the effect on growth was primarily attributed to the biomass reduction in LL while the effect on number of plants was much smaller. Total Chl and Cars contents were decreased in plants exposed to HL which indicated long-term acclimation response to the increased irradiance. Furthermore, the HL plants revealed better capability for the utilization of absorbed light in photosynthesis accompanied by photoprotective adjustment of certain number of PSII reaction centers from active to dissipative mode of functioning. In conclusion, our study showed that duckweed plants had great adjustment potential to different irradiation conditions, which might be of great importance not only under variable light availability but also when simultaneously challenged by some other environmental disturbance (e.g. different pollutants).